Efeito gastroprotetor do óleo essencial da Croton argyrophyllus Kunth e mecanismos de ação farmacológicos em camundongos e lagomorfos - Amorim, Graziele Pereira de (2017)
The species Croton argyrophyllus Kunth possesses an essential oil, composed of terpenes, flavonoids and alkaloids that has anti-inflammatory, antiulcerous antioxidant and analgesic activity, being thus a causative agent with gastroprotective action. Thus, the present study investigated the gastroprotective action of OE Of C. argyrophyllus (1, 3 and 10 mg / kg, vol) and the mechanisms of pharmacological action to this gastroprotective effect in acute acid induced ethanol induced ulcers in Swiss and male Swiss mice. In addition, the ability of this OE (1, 3, 10, 30 and 100 μg / mL) to inhibit K +, H + -ATPase pump activity was investigated in which homogenate prepared from rabbit gastric mucosa To isolate gastric microsomes. OE of C. argyrophyllus (1, 3 and 10 mg / kg) produced dose-dependent gastroprotection, reducing (P <0.001) the total and relative areas of the lesion in the acidified ethanol-induced ulcer model. The gastroprotective response caused by OE (3 mg / kg) was significantly attenuated (P <0.001) by the intraperitoneal treatment of the mice with yohimbine, N-ethylmaleimide (NEM), glibenclamide and indomethacin. The gastroprotection response of OE (3 mg / kg) was also reversed (P <0.01) by intraperitoneal pretreatment of mice with Nw-nitro-L-arginine methyl ester hydrochloride (L-NAME). The EO of the leaves of C. argyrophyllus (10, 30 and 100 μg / mL) was able to inhibit concentration of the proton pump activity (K +, H + -ATPase) in 37.0%, 80.5% and 76.8%, respectively (P <0.01), when using microsomes of the rabbit gastric mucosa. Collectively, the results demonstrate that C. argyrophyllus OE has gastroprotective and antisecretory activity. The results show that the essential oil of C. argyrophyllus has gastroprotective activity and the ability to inhibit proton pump activity.